(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
A wound is a break in the integrity of the skin or tissues often which may be associated with disruption of the structure and function. Globally, the magnitude of acute wounds as a healthcare problem is sharply rising mainly due to industrialization. There is still a need to revisit the ancient healing methods by using traditional medicine aiming to discover a wound healing drug with better protection, rapid granulation changes, least side effects, good bio-availability and low cost. A folk medicinal plant Humboldtia vahliana Wight. belongs to the family Fabaceae, is a medium sized tree with rough, dark brown bark mottled with white. Its stem bark is used for wound healing among the tribes. Aims and objectives: The study aims to evaluate the in-vivo wound healing action of Humboldtia vahliana Wight. through excision and incision animal wound models. Methodology: 36 male Wistar albino rats weighing 150-250gm. were selected and made into 3 groups each for both incision and excision wounds, i.e., control, standard and trial group -each containing 6 rats. The trial drug Humboldtia vahliana Wight. was applied over the wound area in the form of ‘Kalka’. In excision wound model, percentage of wound contraction was the parameter for the study and was achieved by using Planimetry. In incision wound model, tensile strength was the parameter and was achieved by Local Tensiometer. Results: In case of both Incision as well as Excision wound contraction study, the data shows a statistically non-significant increase in percentage wound contraction of Trial group when compared to Control and Standard groups. Interpretation and Conclusion: The stem bark of Humboldtia vahliana Wight. showed better wound healing action in Wistar albino rats when percentage of efficacy or mean values were compared